The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1159/000126725
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms in Reproductive and Thyroid Hormones in Gonadally Regressed Male Hamsters Exposed to Natural Autumn Photoperiod and Temperature Conditions

Abstract: Two groups of young adult male Syrian hamsters were kept in a vivarium at 22°C and a light :dark cycle of 14.5:9.5 h (lights on 06.30 h; indoor) or in a naturally decreasing photoperiod and fluctuating ambient temperature conditions (outdoor) from October 1 (day length 11 h 50 min) to November 30 (day length 10 h 12 min). Representative animals from each group were killed at 3-hour intervals with additional time points near the onset of light. Weights of the paired gonads and accessory organs revealed that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
(29 reference statements)
1
6
0
1
Order By: Relevance
“…The present results concerni n g a v i a n t e s t e s c l e a r l y d e m o n s t r a t e d n o spermatogenesis in seminiferous tubules in the treatment group compared with the control group. This finding is similar to that in other animals, such as in male rats [29,30], male guinea pigs [31] and male hamsters [32][33][34]. In rats, previous reports have demonstrated that hypothyroidism inhibits steroidogenesis [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…The present results concerni n g a v i a n t e s t e s c l e a r l y d e m o n s t r a t e d n o spermatogenesis in seminiferous tubules in the treatment group compared with the control group. This finding is similar to that in other animals, such as in male rats [29,30], male guinea pigs [31] and male hamsters [32][33][34]. In rats, previous reports have demonstrated that hypothyroidism inhibits steroidogenesis [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…Localization of haPer1 and/ or PER1 protein to particular cell types in hamster testis may help to explain apparent species differences and suggest a physiological role of period gene expression in testicular function. Syrian hamsters exhibit significant (twofold) daily rhythms of testosterone secretion (Vaughan et al, 1994), whereas the expression of such rhythms in mice varies with strain (Lucas and Eleftheriou, 1980). Despite the fact that Per1 expression is concentrated in the seminiferous tubules rather than the interstitial tissue, it may be functionally related to androgen production.…”
Section: Discussionmentioning
confidence: 99%
“…De fato, foram medidas, no início do período claro concentrações mais altas do que no início do período escuro, o que sugere um ciclo circadiano de variação da concentração sanguínea de testosterona com acrofase 12 horas antes, ou seja, no início da noite. Este resultado está de pleno acordo com o ritmo circadiano da produção de testosterona relatado na literatura para o hamster macho (Vaughan et al 1994). Na mesma espécie, prazos de 5 a 25 horas foram relatados para metabolização e excreção de esteróides ovarianos (Chelini et al 2005) e de 20 horas para o aparecimento nas fezes dos machos do sinal da elevação dos níveis de glicocorticóides em resposta a um desafio por ACTH (Chelini et al 2010).…”
Section: Discussionunclassified